Is biomass ash an effective product for use in cereal crops in an agroecological system? (Revista de Ciências Agroveterinárias, 2018)
The objective of this study was to evaluate, for four years, the ability of biomass ash (BA) to be used as a tool for developing soil fertility in a system of cereal production in an agroecological base. An experiment with a randomized complete block design with three replications was conducted. The treatments consisted of 0, 2, 4, 6, 8 and 10 Mg ha-1 of ash biomass. The area was corrected and cultivated with a cocktail of green manure species during summer and winter. Soon after the treatments, the following sequence of crops was initiated: corn; vetch; oats + vetch; corn; oats; soy, all without any use of fertilizers. After the first and fourth harvests, soil samples in the 0-0.20 m layer were collected for analysis of fertility attributes. There was a linear increase in P and K content in the soil with the addition of biomass ash. There were no effects of treatments for pH, Ca and Mg and heavy metal content of soil. Corn and soybean yields were not affected by ash biomass application in any year. Thus, the use of BA does not present harmful effects to agroecological production systems and is a safe source of K, since the absence of non-soluble sources is one of the limitations for the supply of this nutrient to crops.
Keywords: green manure; soil management; waste; sustainability